Concomitant bladder and rectal injuries: Results from the American Association for the Surgery of Trauma Multicenter Rectal Injury Study Group. Issue 2 (February 2020) - Osterberg, E. Charles; Veith, Jacob; Brown, Carlos V. R.; Sharpe, John P.; Musonza, Tashinga; Holcomb, John B.; Bui, Eric; Bruns, Brandon; Hopper, H. Andrew; Truitt, Michael; Burlew, Clay Cothren; Schellenberg, Morgan; et al.
Abstract : BACKGROUND: Combined traumatic injuries to the rectum and bladder are rare. We hypothesized that the combination of bladder and rectal injures would have worse outcomes than rectal injury alone. METHODS: This is an American Association for the Surgery of Trauma multi-institutional retrospective study from 2004 to 2015 traumatic rectal injury patients who were admitted to one of 22 participating centers. Demographics, mechanism, and management of rectal injury were collected. Patients who sustained a rectal injury alone were compared with patients who sustained a combined injury to the bladder and rectum. Multivariable logistic regression was used to determine if abdominal complications, mortality, and length of stay were impacted by a concomitant bladder injury after adjusting for cofounders. RESULTS: There were 424 patients who sustained a traumatic rectal injury, of which 117 (28%) had a combined injury to the bladder. When comparing the patients with a combined bladder/rectal injury to the rectal alone group, there was no difference in admission demographics admission physiology, or Injury Severity Score. There were also no differences in management of the rectal injury and no difference in abdominal complications (13% vs. 16%, p = 0.38), mortality (3% vs. 2%, p = 0.68), or length of stay (17 days vs. 21 days, p = 0.10). When looking at only the 117 patients with a combined injury, the addition of a colostomy did not significantly decrease the rate of abdominal complications (14% vs. 8%, p = 0.42), mortality (3% vs. 0%, p = 0.99), or length of stay (17 days vs. 17 days, p = 0.94). After adjusting for cofounders (AAST rectal injury grade, sex, damage-control surgery, diverting colostomy, and length of stay) the presence of a bladder injury did not impact outcomes. CONCLUSION: For patients with traumatic rectal injury, a concomitant bladder injury does not increase the rates of abdominal complications, mortality, or length of stay. Furthermore, the addition of a diverting colostomy for management of traumatic bladder and rectal injury does not change outcomes. LEVEL OF EVIDENCE: Level IV; prognostic/therapeutic.